67.1k views
2 votes
Which expression is equivlaent to (9x - 3 1/8) - (7x + 1 3/8)

A 2x - 4 1/2
B 16x - 4 1/2
C 2x - 1 3/4
D 16x - 1 3/4

User Megamug
by
7.2k points

1 Answer

7 votes
If you would like to know which expression is equivalent to (9 * x - 3 1/8) - (7 * x + 1 3/8), you can calculate this using the following steps:

(9 * x - 3 1/8) - (7 * x + 1 3/8) = 9 * x - 3 1/8 - 7 * x - 1 3/8 = 2 * x - 25/8 - 11/8 = 2 * x - 36/8 = 2 * x - 4 4/8 = 2 * x - 4 1/2

The correct result would be A. 2 * x - 4 1/2.
User FlySwat
by
7.4k points